2022
DOI: 10.1021/acsmaterialsau.2c00014
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printed MoS2/Graphene Aerogel Electrodes for Hydrogen Evolution Reactions

Abstract: In this work, we demonstrate the use of direct ink writing (DIW) technology to create 3D catalytic electrodes for electrochemical applications. Hybrid MoS2/graphene aerogels are made by mixing commercially available MoS2 and graphene oxide powders into a thixotropic, high concentration, viscous ink. A porous 3D structure of 2D graphene sheets and MoS2 particles was created after post treatment by freeze-drying and reducing graphene oxide through annealing. The composition and morphology of the samples were ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…3D-printing technology has shown exceptional advancement in several domains, with its major potential in recent years being the fabrication of electrochemical devices and cells for electrochemical applications. For instance, there are several existing reports available on using 3D-printed electrode substrates for catalysis applications through modifications, patterning, functionalization, or by integrating active materials for hydrogen evolution reaction (HER) [28,[87][88][89][90] and oxygen evolution reactions (OER). [89][90][91] With the advancements in technology, rapid prototyping of 3D-printed substrates of specific geometry and composition can aid in successful 3D-printing of active structures beyond catalyst.…”
Section: Other 3d-printing Techniquesmentioning
confidence: 99%
“…3D-printing technology has shown exceptional advancement in several domains, with its major potential in recent years being the fabrication of electrochemical devices and cells for electrochemical applications. For instance, there are several existing reports available on using 3D-printed electrode substrates for catalysis applications through modifications, patterning, functionalization, or by integrating active materials for hydrogen evolution reaction (HER) [28,[87][88][89][90] and oxygen evolution reactions (OER). [89][90][91] With the advancements in technology, rapid prototyping of 3D-printed substrates of specific geometry and composition can aid in successful 3D-printing of active structures beyond catalyst.…”
Section: Other 3d-printing Techniquesmentioning
confidence: 99%
“…A recent study demonstrated the use of DIW to fabricate a porous 3D printed graphene sheet/MoS 2 aerogel as the cathodic material for H 2 evolution reaction. 111 The 3D printed porous network, which exhibited 1–2 nm of pore diameter, had shown to be a robust functionalised aerogel that provided multidimensional electron transport channels that improved the electronic conductivity; electrolyte dispersion that facilitated catalyst utilization.…”
Section: Printing Of Functional Materials By Diwmentioning
confidence: 99%
“…[32] Chandrasekaran et al prepared a viscous MoS 2 /graphene ink and printed a porous 3D structure of 2D graphene sheets and MoS 2 particles with good mass transport of gas products for electrochemical catalytic reactions, such as water splitting. [97] However, 2D carbon materials are significantly more expensive than porous carbon, making widespread applications challenging.…”
Section: Carbon Materialsmentioning
confidence: 99%